The Aesthetics of a Three-Way Pattern: The Musical Concept of Talempong Renjeang and The Social System of The People of Luhak Nan Tigo Minangkabau - Andar Indra Sastra (Humaniora, 2017)
The goal of this article is to discuss the aesthetics of the three-way pattern in the musical concept of  talempong renjeang (tenteng) and the social system of the people of Luhak Nan Tigo Minangkabau. The musical concept of talempong renjeang is formed by 3 (three) pairs of  talempong: talempong Jantan, talempong Paningkah, and talempong Pangawinan. As the ‘leader’, the talempong Jantan maintains the consistency and integrity of the theme and danyuik (tempo) of the playing, the talempong Paningkah follows the lead of the talempong Jantan using different playing motifs, and the talempong Pangawinan has the role and authority to make the guguah (melody) of the talempong complete – creating a three-way aesthetical pattern. The social system of the people of LuhakNan Tigo was created by three legendary figures, namely Dt. Katumangguangan, Dt. Parpatiah Nan Sabatang, and Dt. Nan Sakelap Dunia (RajoBabandiang). From these three figures, the concept of tali tigo sapilin, tungku nan tigo sajarangan was born (a philosophy of harmony). The method used for the research is based on qualitative data which was collected through observation, interviews, and documentation. The data analysis focuses the talempong renjeang as a musical and the social system of the Minangkabau community which began with two legendary Minangkabau figures. The results of the study show that talempong as a musical system corresponds to, or synchronizes with, the social concept of the people of Luhak Nan Tigo Minangkabau.